SINTESIS DAN KARAKTERISASI SUPERABSORBEN DARI SELULOSA JERAMI PADI (Superabsorbent Synthesis and Characterization of Rice Straw Cellulose) - Wina Yulianti; Farida Laila (IPB University, 2014)
Copolymerization of cellulose from rice straw with acrylic acid and acrylamide produce biopolymer superabsorbent. Cellulose was purified from fat content by extraction with toluene:ethanol (2:1). Hemicelluloses and lignin were removal by using potassium hydroxide 5% and hydrogen peroxide 2% at alkaline pH. Cellulose yield obtained was 21.56%. FTIR spectra of lignin showed a loss of absorption at 1728 cm-1. Copolymerization was carried out at 65 C under nitrogen athmosphere. Initiator and cross linking agent used were potassium peroxodisulfate and N'N-methylene bis acrylamide. Superbasorben resulted from this experiment showed the water swelling capacity after 24 hour for the water, solution of 100 ppm of ammonium chloride, and urea respectively 387,11 g/g ; 193,47 g/g and 400,17 g/g.Keywords : superabsorbent, rice straw, swelling capacity